Working Towards Green Tourism Accreditation at Dawyck Botanic Garden: a Case Study - Stewart, Graham (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2011)
Dawyck Botanic Garden was awarded a Silver accreditation in the Green Tourism Business Scheme in December 2010. The award was the result of a sustained focus to pursue an industry award as a measure of Dawyck’s achievements in sound environmental management. The award followed the construction of a new Visitor Centre in 2008 and also built upon green initiatives already achieved by staff. This case study follows the stages of the process up to the point of the award being made.